Comunicação interna nas empresas juniores: estudo das estratégias de comunicação da Objetiva Júnior do curso de administração da Universidade Federal de Santa Maria/RS - (:unkn) unknown (Universidade Federal do Pampa, 2019)
With technological advances the companies, in general, has searching strategies to make the organizational environment more attractive for your internal public and promote an effective communication.For this reason, the internal communication have strongly influenced the organization, which in turn, are embedded in a globalized context, Dynamic and competitive. In this sense our research has intention to understand how the internal communication works in a junior company and your advantage to the same, Linked at this we have as target to verify which strategies of internal communication can contribute for a junior company achieve the organizational goals.As methodological path, we start from the bibliographic research with the development of exploratory research, with a qualitative-quantitative approach, our data collection was divided into three stages, first one observatory, after applying an interview with two directors of the company, our last stage were the questionnaires, one designed for leadership and the other to production members, the first questionnaire had five respondents and the second with twenty-two respondents. In between the main results are possible conclude that internal communication is already seen as a strategic tool and that an organized working environment integrate and encourages the team, is perceived that electronic means stand out when the question is usability, channels such as e-mail and social network are the most used,in them the members become participatory and knowledge about the team makes it easy to plan communication,About everything seek to be transparent with who works in the company only has to aggregate, Noting that these results are important for organizational purposes.
Keywords: Ensino superior; Comunicação nas organizações; Higher education; Communication in organizations; CNPQ::CIENCIAS SOCIAIS APLICADAS